KRITIK SASTRA OBJEKTIF PADA KUMPULAN PUISI HUJAN BULAN JUNI KARYA SAPARDI DJOKO DAMONO - Pranata, Jodi; Widianti, Agustina; Astuti, Merliana Kusuma; Diana, Ani (Prawara: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2023)
This research aims to determine the strengths and weaknesses of the poetry collection "June Rain" by Sapardi Djoko Damono. This research uses a qualitative research method, library research. The theory used in research uses objective critical theory. The results of this research show that the collection of poems by Djoko Damono entitled "June Rain" contains many strong religious values, about the relationship between humans and God, which are conveyed in an advisory tone, in a solemn and solemn atmosphere, to provide advice to the reader. The weakness of the poetry collection "June Rain" by Sapardi Djoko Damono lies in its use of diction which uses a lot of symbolic and figurative styles so that it will be difficult for lay readers to understand it. The conclusion of this research is that the collection of poems "June Rain" by Sapardi Djoko Damono is very interesting to read because it contains many religious values which can be used as a reflection in everyday life. Keywords: Objective Criticism, Physical and Inner Structure, Poetry